2015
DOI: 10.1002/adfm.201500034
|View full text |Cite
|
Sign up to set email alerts
|

TAPE: A Medical Adhesive Inspired by a Ubiquitous Compound in Plants

Abstract: Adhesives play an important role in industrial fields such as electronics, architectures, energy plantation, and others. However, adhesives used for medical purpose are rather under‐developed compared with those used in industry and consumer products. One key property required for medical adhesives is to maintain their adhesiveness in the presence of body fluid. Here, an entirely new class of medical adhesives called TAPE is reported; this is produced by intermolecular hydrogen bonding between a well‐known pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
240
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 259 publications
(247 citation statements)
references
References 29 publications
7
240
0
Order By: Relevance
“…[9,10] Notwithstanding the exciting successes,t he preparation of those materials usually involves multi-step procedures,t ime consuming process, harsh conditions,a nd toxic reagents.T hese synthetic chal-lenges and environmental concerns prompt scientists to seek natural substitutes.R ecently,L ee and co-workers have reported as imple strategy to produce wet adhesive (TAPE) via co-assembly of tannic acid and poly(ethylene glycol) in water. [11] Ther esulted adhesive showed higher adhesion strengths than that of the commercially available fibrin glue. Theauthors also demonstrated that the TAPE adhesives can act as an effective hemostatic material for detecting gastroesophageal reflux disease in vivo.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…[9,10] Notwithstanding the exciting successes,t he preparation of those materials usually involves multi-step procedures,t ime consuming process, harsh conditions,a nd toxic reagents.T hese synthetic chal-lenges and environmental concerns prompt scientists to seek natural substitutes.R ecently,L ee and co-workers have reported as imple strategy to produce wet adhesive (TAPE) via co-assembly of tannic acid and poly(ethylene glycol) in water. [11] Ther esulted adhesive showed higher adhesion strengths than that of the commercially available fibrin glue. Theauthors also demonstrated that the TAPE adhesives can act as an effective hemostatic material for detecting gastroesophageal reflux disease in vivo.…”
mentioning
confidence: 86%
“…[8] Thea dhesives have significant potentials in other biomedical devices that require haemostatic treatment. [11] Ther esulted adhesive showed higher adhesion strengths than that of the commercially available fibrin glue. [9,10] Notwithstanding the exciting successes,t he preparation of those materials usually involves multi-step procedures,t ime consuming process, harsh conditions,a nd toxic reagents.T hese synthetic chal-lenges and environmental concerns prompt scientists to seek natural substitutes.R ecently,L ee and co-workers have reported as imple strategy to produce wet adhesive (TAPE) via co-assembly of tannic acid and poly(ethylene glycol) in water.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…TA, a natural polyphenol, endows the coatings with high binding affinity to different substrates and antioxidant capacities . TAs associate with PEGs into stable micrometer‐sized complexes through intermolecular hydrogen bond in neutral or acidic aqueous solution . With addition of NaCl, these complexes rapidly precipitate onto substrates under gravity and coalesce with each other to generate uniform soft coatings via hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%